Internal Quality Assurance System of Private Islamic Religious Higher Education Institutions in Improving the Quality of Lecturers: A Case Study of IAI Nusantara Batang Hari Jambi - Qori Kartika; Adrianus Chatib; Abdul Malik (Yayasan Adra Karima Hubbi, 2024)
Lecturers are the primary instruments in the implementation of the tri dharma, whose quality can be measured through academic rank attainment, educator certification, and doctoral education. To enhance the quality standards of lecturers, it can be done through the implementation of an internal quality assurance system (SPMI) that must be carried out systematically and continuously. “Data collection was carried out through documentation, interviews, and observation. Data analysis was conducted using the interactive analysis model (Miles and Huberman, 2014), and data validity was tested through triangulation to verify the accuracy of the data. The conclusion of this research is (1) the quality of lecturers at IAI Nusantara Batang Hari Jambi in the implementation of tri dharma in the fields of teaching, research, and community service has been running well according to the established regulations, (2) the implementation of SPMI at IAI Nusantara Batang Hari Jambi in the form of planning, execution, evaluation, control, and improvement is still carried out in a simple manner. In this case, only the planning and execution cycles have been implemented, while the evaluation cycle in the form of internal quality audits, the control cycle through management review meetings, and improvement efforts have not yet been conducted, (3) the choice of SPMI model implemented by IAI Nusantara Batang Hari Jambi is not very appropriate for small management and limited resources, as well as minimal financial support. Ideally, the selected SPMI model should integrate SPMI management with university management.